Crescimento e produção de fitomassa da mamoneira BRS energia adubada com nitrogênio e silício - Figuerêdo, Djalma José Correia de (2013)
Silica can stimulate the uptake of N by plants, resulting in improved leaf architecture and greater use of light, and therefore more productive plants. In this sense, the objective of this experiment was to evaluate the effects of the interaction between Si and N on growth, dry matter yield and mineral composition of castor bean plants BRS Energy. The experiment was conducted at Embrapa Cotton in Campina Grande-PB, with treatments arranged in a randomized complete block design with factorial arrangement (4x4), four doses of silicon (00, 80, 160, 240 mg L-1) and four nitrogen rates (00, 60, 120, 180 kg ha-1) applied per plant, with four repetitions, totaling 64 experimental units. Despite the increase of N levels decrease K content in the soil , stimulated the growth of other variables , stem diameter , number of leaves and leaf area . Silicon fertilization foliar provided a significant increase in stem diameter , with the highest value ( 18,54 mm ) due to the higher dose of Si applied . The absolute growth rate in stem diameter reached a maximum value of 0,068 mm.day-1 corresponding to 100 kg ha-1 N. The absolute growth rate for leaf area during the study period , set the quadratic model , with increasing increments as a function of N rates , with higher value of 20,60 cm2.dia-1 at a dose of 102,63 kg ha-1. The increasing up to a maximum of 99,43 kg ha-1 N , gave a ratio of leaf area of 19,85 cm2 per gram of dry matter produced by the plant . The N content in the leaves increased as a function of N rates , an increase in leaf content of 4,76 % observed at the dose of 118,75 kg ha-1 N. The total dry mass reached 134,99 g plant-1 , depending on the dose of 109,79 kg ha-1 of nitrogen.